Nilai Pendidikan Islam Dalam Nganggung Sebagai Pelestarian Budaya di Kelurahan Tua Tunu - Ina Afriana (4, 2025)
Local culture is a crucial foundation for shaping the identity and character of a community, and it must be preserved amidst the currents of globalization that threaten its sustainability. The Nganggung tradition in Tua Tunu Village is one manifestation of local culture, embodying noble values ​​and local wisdom that align with the principles of Islamic education. This study analyzes the values ​​of Islamic education in Nganggung culture, its implementation in Tua Tunu Village, and its implications for cultural preservation. Using a descriptive qualitative approach with a case study method, data were collected through interviews (with traditional leaders, religious leaders, Islamic Religious Education teachers, youth, and the community), participant observation, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldana, with source triangulation. The results show that Nganggung integrates religious values ​​(gratitude, almsgiving, communal prayer), moral values ​​(politeness, mutual cooperation, simplicity), and social values ​​(silaturahmi, solidarity). Effective implementation is achieved through social communication, voluntary participation, community commitment, and government support. Theoretical implications include local Islamic acculturation for anthropological/sociological studies; practical implications include strengthening socio-economic ties, instilling noble values ​​in the younger generation, and tourism potential. The Nganggung tradition strengthens religious, moral, and social values, serving as an effective means of transmitting Islam, mutual cooperation, and harmony. Government support and youth involvement are crucial for its sustainability in the modern era. Abstrak Budaya lokal merupakan fondasi penting dalam membentuk identitas dan karakter suatu masyarakat, yang perlu dilestarikan di tengah arus globalisasi yang mengancam keberlangsungannya. Tradisi nganggung di Kelurahan Tua Tunu merupakan salah satu wujud budaya lokal yang mengandung nilai-nilai luhur dan kearifan lokal yang selaras dengan prinsip pendidikan Islam. Penelitian ini menganalisis nilai-nilai pendidikan Islam dalam budaya Nganggung, implementasinya di Kelurahan Tua Tunu, serta implikasinya terhadap pelestarian budaya. Menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus, data dikumpul melalui wawancara (tokoh adat, agama, guru PAI, generasi muda, masyarakat), observasi partisipan, dan dokumentasi. Analisis data mengikuti model interaktif Miles, Huberman, dan Saldana, dengan triangulasi sumber. Hasil menunjukkan bahwa Nganggung mengintegrasikan nilai agama (syukur, sedekah, doa bersama), akhlak (kesopanan, gotong royong, kesederhanaan), dan sosial (silaturahmi, solidaritas). Implementasi efektif melalui komunikasi sosial, partisipasi swadaya, komitmen warga, dan dukungan pemerintah. Implikasi teoretis mencakup akulturasi Islam-lokal untuk kajian antropologi/sosiologi; praktis, mempererat hubungan sosial-ekonomi, menanamkan nilai luhur pada generasi muda, dan potensi pariwisata. Tradisi Nganggung memperkuat nilai agama, akhlak, dan sosial, sebagai sarana efektif transmisi Islam, gotong royong, dan kerukunan. Dukungan pemerintah dan keterlibatan pemuda krusial untuk keberlanjutannya di era modernisasi